The Epidemiology of Lung Cancer in Lebanon During 2014 - Rida Salman; Khairallah Amhaz; Ali Hellani; Loubna Tayara; Batoul Mourda (Shahrekord University of Medical Sciences, 2020)
Background and aims: Lung cancer is the leading cause of cancer death worldwide. There are no recent data on the lung cancer prevalence in Lebanon, and the available data are based on prediction. Thus, this study aimed to determine the incidence rate of lung cancer during 2014, among patients who were newly diagnosed at Lebanese teaching hospitals. In addition, the study attempted to identify the associated risk factors of lung cancer, the most common presenting symptoms at the diagnosis time, and the stage at which the majority of the patients were diagnosed at the targeted population. Methods: A retrospective cross-sectional study was carried out in many teaching hospitals affiliated to the Lebanese University in Lebanon in 2016. Results: The lung cancer incidence was 221.9 per 100000 in 2014. Most patients aged 60 years and over and as regards gender distribution, the majority of them included men. Further, more than half of the patients had the (COPD) and 97% of patients had symptoms at their presentation. Based on the results, 57.9% of them had stage IV lung cancer, but only 12% were diagnosed at the stage IA. Furthermore, 80.6% and 16.4% of patients had non-small and small cell lung cancer, respectively. Finally, 75.4% and 12.1% of them were treated with chemotherapy and underwent surgery, respectively, while 5.2% of patients had radiotherapy. Conclusion: The findings of our study showed a higher incidence rate of lung cancer since 2008 which was diagnosed more commonly in men and with the patient's history of COPD. Eventually, the diagnosis was mostly made at a later stage with non-small cell lung cancer that was the most common histology type.